MODEL OF SCHOOL MANAGEMENT BASED ON CHARACTER BUILDING IN SCHOOL CULTURE - Udik Budi Wibowo, Arita Marini, Desy Safitri, Apri Wahyudi (International Journal of Advanced Science and Technology, 2020)
This research aim at offering a model of school management based on character building in school culture for elementary schools in Jakarta in Indonesia. This research conducting survey method distributing the questionnaires to 293 elementary school students grade five in Jakarta in Indonesia. Analysis technique in this research used Structural Equation Modeling (SEM). The research found that the model of school management based on character building in school culture offered was good fit for the data. The result of study stated that religious school culture, honest school culture, discipline school culture, and clean and healthy school culture have positive connection with character building on the basis of school culture. Based on research findings, it can be concluded that a model of school management based on character building in school culture proposed can be used for elementary schools in South Jakarta in Jakarta in Indonesia.